Effect of drain pipes on seepage and slope stability through a zoned earth dam - Hassan Waqed H.; Atshan Thaer T.; Thiab Rifqa F. (Open Engineering)
Earth dams must be supplied with seepage control devices to prevent piping and sloughing. One such device used for this purpose is the so-called drain pipe. This study focuses on the influence of drain pipes on seepage and slope stability analysis in a zoned earth dam; here, for the specific case study of the Al-Adhaim dam, Iraq. The purpose of this study is to demonstrate the beneficial effects of drain pipes in the control of seepage and improving slope stability in zoned earth dams, thus allowing for specific recommendations for the optimal location(s) of any drain pipes. SEEP/W software was used to evaluate the steady-state seepage that occurs through and beneath the dam, and SLOPE/W software was used to analyze slope stability. In this study, two drain pipes, each with diameters of 15 cm, were used in the earth dam, with a vertical distance of 1 m between them. The effects of the drain pipes through the earth dam were investigated by varying their relative locations, specifically at X/B = 0.5, 0.6, and 0.7. The results of the study showed that the presence of the drain pipes was effective in reducing the elevation of the phreatic surface line. Additionally, the drain pipes significantly reduced the seepage flow and hydraulic exit gradient while increasing the factor of safety (FOS). Based on the findings, it was concluded that the most effective position for the drain pipes was when they were located at X/B = 0.7; in this configuration, they allowed for minimum seepage flow (70%) and hydraulic exit gradient (72%), while providing the highest FOS (17.2).